Incitement through the Media - Mansour Rashid, Researcher. Sara; Jabbar Craidy, Prof.Dr. Ali (Basra studies journal, 2025)
This research addresses the concept of media incitement from a legal perspective by analyzing the regulatory framework governing it at both national and international levels. It clarifies the boundary between freedom of expression, as a right guaranteed in international conventions and national legislations, and unlawful media incitement, which poses a threat to public order and social peace. Media incitement is a complex legal phenomenon involving the use of media, whether traditional or digital, to disseminate messages that encourage individuals or groups to commit acts of violence, hatred, or discrimination against certain groups, thereby threatening social and international stability. This incitement manifests in various forms across both traditional and digital media, with online platforms facilitating the rapid dissemination of ideas and information that may be inciting. At the international level, media incitement intersects with the right to freedom of expression, a fundamental right guaranteed in numerous international legal instruments, such as the International Covenant on Civil and Political Rights. While freedom of expression is a core right, international law imposes strict limitations on media incitement that leads to violence or discrimination, in order to protect social peace and human rights. It also encompasses the legal standards applied by courts to determine when media speech constitutes incitement to violence or hatred and is therefore subject to criminalization under international law.